Association of Academic Physiatrists Federal Funding of Disability and Rehabilitation Research Position Statement. (August 2018) - Whyte, John
Abstract : Abstract: The Association of Academic Physiatrists seeks to advocate for policies that are supportive of academic rehabilitation, with elected officials, agency leaders, and other policy makers. Accordingly, the Association of Academic Physiatrists' Public Policy Committee identifies policy issues of importance to the organizational mission, conducts background research on those issues, and develops position statements that articulate the organization's position. These position statements require approval by the Board of Trustees and are used to support advocacy efforts by Association of Academic Physiatrists' members. Federal funding for disability and rehabilitation research is an important issue for the Association of Academic Physiatrists and its members. This position statement addresses the need for greater federal funding in this area, better coordination of the agencies providing funding, and an appropriate balance of merit-based funding with funding targeted to building capacity in critical rehabilitation-relevant methodology and content areas.